Islamophobia and Misconception : A Systematic Literature Review (Universitas Muhammadiyah Yogyakarta, 2022)
This research aims to determine the development of the phenomenon of Islamophobia and misconceptions about Islam and Muslims that occur in the world. The research method used is a systematic literature review (SLR) using 580 scientific journal articles from the Scopus database. The article analysis uses RIS Scopus data which is visualized using the Vos Viewer application to determine the co-occurrence of the article data obtained. From the analysis carried out, the results reveal that the study of Islamophobia and Misconceptions has long been a concern of scholars/researchers. This is evidenced by the many relevant topics and sub-themes that exist. This study also concludes that the phenomenon of tidal Islamophobia is following the dynamics of events that occur. The results of this research contribute to describing the magnitude of Islamophobia against Islam and Muslims in the world. This research also contributes as a reminder to the world of the importance of maintaining peace and tolerance. The drawback of this research is that the articles used as authorship references are only sourced from the Scopus database. So that the results presented in this scientific article are not able to fully describe Islamophobia and its misconceptions that occur in the world. From this lack of scientific article writing, it is hoped that further research can use scientific articles sourced from databases of other accredited international journals, such as Web of Science (WoS), Thomson Reuters, Elsevier, and Springer.